The Role of Social Media and Generation Z Identity on Language Variation in Digital Communication - I Wayan Mawa (Eastasouth Institute, 2026)
The rapid development of social media has transformed communication patterns among young people, particularly Generation Z who grew up in a digital environment. Interaction within virtual spaces not only influences communication practices but also shapes linguistic variations used in everyday digital communication. This study aims to analyze the role of social media and the construction of Generation Z identity in shaping language variation in digital communication. The research employs a descriptive qualitative approach using data derived from posts, comments, and other forms of online communication across social media platforms. Data were analyzed through discourse analysis and identification of language variation patterns. The findings indicate that social media functions as a space for the production of new linguistic forms, including slang, code-mixing, abbreviations, and visual symbols. These linguistic variations serve as tools for identity expression, group solidarity, and markers of social proximity. The study highlights that language change in digital spaces represents not only a linguistic phenomenon but also a reflection of generational identity construction in contemporary digital society.